Conflicts of interest: the responsibility of the authors and editors of the International Journal of Cancer - Zur Hausen, Harald; Bartsch, Helmut; Fusenig, Norbert; Knebel Doeberitz, Magnus von; Kyewski, Bruno; Lichter, Peter; Miller, Anthony (International journal of cancer, 2006)
Click on the article title to read more.
Gesehen am 23.11.2020